Study of alkaloids present in the vine of the saragoza (Aristolochia elegans) - Parrales Alay, Anthony Wladimir; Villamar Pibaque, Janice Andreina (Revista Universidad de Guayaquil, 2022)
In Ecuador, Saragoza lily (Aristolochia elegans) is used as an infusion for the treatment of menstrual pains, as well as intestinal infections and diarrhea; in 2020 65.4% of diarrhea cases were in young adults and 7.2% in older adults having varied etiology. A qualitative and quantitative analysis of Saragoza bejuco (Aristolochia elegans) was carried out due to its importance that would demonstrate the presence of alkaloids and their possible antidiarrhealantimicrobial activity. The content of alkaloids present in Saragoza bejuco (Aristolochia elegans) was evaluated through a preliminary phytochemical screening, observing a color reaction and precipitation in the Dragendorff +++, Mayer +++ and Wagner +++ trials indicating the positive presence of alkaloids and also total alkaloids wereindicating the positive presence of alkaloids and likewise they were quantified in the determination of total alkaloids by the spectrophotometric method which resulted in 576.00 mg / L in 70% ethanolic extract, and finally the aristolochic acid was analyzed by the layer chromatography method fine which resulted in the Rf of 0.407 that is within the identification range.